Simple Measures of Function and Symptoms in Hospitalized Heart Failure Patients Predict Short-Term Cardiac Event-Free Survival - Evanthia Zaharias; Janine Cataldo; Lynda Mackin; Jill Howie-Esquivel (Hindawi Limited, 2014)
Background. Heart failure (HF) is a prevalent chronic condition where patients experience numerous uncomfortable symptoms, low functional status, and high mortality rates. Objective. To determine whether function and/or symptoms predict cardiac event-free survival in hospitalized HF patients within 90 days of hospital discharge. Methods. Inpatients (N=32) had HF symptoms assessed with 4 yes/no questions. Function was determined with NYHA Classification, Katz Index of Activities of Daily Living (ADLs), and directly with the short physical performance battery (SPPB). Survival was analyzed with time to the first postdischarge cardiac event with events defined as cardiac rehospitalization, heart transplantation, or death. Results. Mean age was 58.2 ± 13.6 years. Patient reported ADL function was nearly independent (5.6 ± 1.1) while direct measure (SPPB) showed moderate functional limitation (6.4 ± 3.1). Within 90 days, 40.6% patients had a cardiac event. At discharge, each increase in NYHA Classification was associated with a 3.4-fold higher risk of cardiac events (95% CI 1.4-8.5). Patients reporting symptoms of dyspnea, fatigue, and orthopnea before discharge had a 4.0-fold, 9.7-fold, and 12.8-fold, respectively, greater risk of cardiac events (95% CI 1.2-13.2; 1.2-75.1; 1.7-99.7). Conclusions. Simple assessments of function and symptoms easily performed at discharge may predict short-term cardiac outcomes in hospitalized HF patients.